Efficacy evaluation of a new water sanitizer for increasing the shelf life of Southern Australian King George Whiting and Tasmanian Atlantic Salmon fillets. (December 2017) - Khazandi, Manouchehr; Deo, Permal; Ferro, Sergio; Venter, Henrietta; Pi, Hongfei; Crabb, Simon; Amorico, Tony; Ogunniyi, Abiodun D.; Trott, Darren J.
Abstract: The bacterial species and specific spoilage organisms associated with the Southern Australian King George Whiting (KGW) and Tasmanian Atlantic Salmon (TAS), and the efficacy of a HOCl-containing water-based sanitization product (E lectro-C hemicallyA ctivatedS olution, by ECAS4) in extending the shelf life of KGW and TAS fillets were evaluated. Fillets were washed with an ECAS4 solution containing either 45 ppm or 150 ppm of free chlorine and bacterial species enumerated on selective and non-selective media, followed by identification of pure isolates by 16 S rRNA gene sequencing. The dominant spoilage microbiota in KGW and TAS fillets stored at 4 ± 1 °C were Pseudomonas spp. and Shewanella spp. At either concentration, ECAS4 significantly reduced total bacterial load and specific spoilage organisms on KGW and TAS fillets (approx. 1–2 log colony-forming units) during storage and significantly extended the shelf life of the fillets by 2 and 4 days, respectively. The significant increase in shelf life and quality of fillets was corroborated by raw and cooked sensory evaluation. ECAS4 sanitization could have a significant impact on the overall food industry, translating into health and economic benefits through reduction of food spoilage bacteria and potentially, foodborne pathogens without many of the disadvantages of currently approved biocides. Highlights: A HOCl-containing water sanitization product (ECAS4) for fish fillets is described. ECAS4 significantly reduced specific spoilage and total bacterial load on fillets. ECAS4 treatment significantly extended the shelf life of fish fillets. Use of ECAS4 sanitization did not diminish the raw or cooked qualities of fillets. The product has potential for widespread use in the overall food industry.